Post-COVID-19 condition: a sex-based analysis of clinical and laboratory trends - Delfino, Carlos; Poli, M. Cecilia; Vial, Cecilia; Vial, Pablo A.; Martínez, Gonzalo; Riviotta, Amy; Arbat, Catalina; Mac-Guire, Nicole; Hoppe, Josefina; Carvajal, Cristóbal; Muñoz Venturelli, Paula (Frontiers in Medicine, 2024)
Background and aim Post-COVID-19 condition (PCC) encompasses long-lasting symptoms in individuals with COVID-19 and is estimated to affect between 31–67% of patients, with women being more commonly affected. No definitive biomarkers have emerged in the acute stage that can help predict the onset of PCC, therefore we aimed at describing sex-disaggregated data of PCC patients from a local cohort and explore potential acute predictors of PCC and neurologic PCC. Methods A local cohort of consecutive patients admitted with COVID-19 diagnosis between June 2020 and July 2021 were registered, and clinical and laboratory data were recorded. Only those <65 years, discharged alive and followed up at 6 and 12 months after admission were considered in these analyses. Multivariable logistic regression analysis was performed to explore variables associated with PCC (STATA v 18.0). Results From 130 patients in the cohort, 104 were contacted: 30% were women, median age of 42 years. At 6 months, 71 (68%) reported PCC symptoms. Women exhibited a higher prevalence of any PCC symptom (87 vs. 60%, p = 0.007), lower ferritin (p = 0.001) and procalcitonin (p = 0.021) and higher TNF levels (p = 0.042) in the acute phase compared to men. Being women was independently associated to 7.60 (95% CI 1.27–45.18, p = 0.026) higher risk for PCC. Moreover, women had lower return to normal activities 6 and 12 months. Conclusion Our findings highlight the lasting impact of COVID-19, particularly in young women, emphasising the need for tailored post-COVID care. The lower ferritin levels in women are an intriguing observation, warranting further research. The study argues for comprehensive strategies that address sex-specific challenges in recovery from COVID-19.